If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4w + -5) + 6w = 4 + 5(2w + -2) Reorder the terms: -2(-5 + 4w) + 6w = 4 + 5(2w + -2) (-5 * -2 + 4w * -2) + 6w = 4 + 5(2w + -2) (10 + -8w) + 6w = 4 + 5(2w + -2) Combine like terms: -8w + 6w = -2w 10 + -2w = 4 + 5(2w + -2) Reorder the terms: 10 + -2w = 4 + 5(-2 + 2w) 10 + -2w = 4 + (-2 * 5 + 2w * 5) 10 + -2w = 4 + (-10 + 10w) Combine like terms: 4 + -10 = -6 10 + -2w = -6 + 10w Solving 10 + -2w = -6 + 10w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-10w' to each side of the equation. 10 + -2w + -10w = -6 + 10w + -10w Combine like terms: -2w + -10w = -12w 10 + -12w = -6 + 10w + -10w Combine like terms: 10w + -10w = 0 10 + -12w = -6 + 0 10 + -12w = -6 Add '-10' to each side of the equation. 10 + -10 + -12w = -6 + -10 Combine like terms: 10 + -10 = 0 0 + -12w = -6 + -10 -12w = -6 + -10 Combine like terms: -6 + -10 = -16 -12w = -16 Divide each side by '-12'. w = 1.333333333 Simplifying w = 1.333333333
| y=45x+3 | | 3s^3-2s^2-3s+2=0 | | 4v-16=56 | | 21=-3/2(18)-19 | | -2(4y-5)=34 | | 7(8r-2)-8(3r+4)I= | | 3/5a=33 | | .6a-1.6=.2a+.4 | | 9w+18=3(w-8) | | 2x+y=5-5x-2y+-6 | | -26-3x=x+30 | | 5t*t-12t-12=0 | | -5(v+9)=5v+5 | | f(2.4)=2x^2-3x+5 | | 2y/3=3.9 | | solver-15r+3=r-2+7(8-4r) | | 4x-11y+16=0 | | 12p+11q+p-4q-4p= | | -9v+34=6(v+6) | | 5(u-89)=35 | | -3x-(4)=14 | | 4+5=x+9 | | -12-5x=27-2x | | 3y+5x=14 | | 7(c-1)+4=11 | | 8v+34=6(v+6) | | 0.3(5+2x)+1.3x=3.3 | | 5.4+0.2x=-1.4x+8.4 | | 4(b+2)=24 | | 3x-42=-2x+28 | | -6(u-1)=-2u+22 | | 2ax-6=0 |